Assessment of Multiple Reference Frame (MRF) and Sliding Mesh methods on a brake system and wheel model - Arteaga Montenegro, Daniel A. (Cranfield University, 2025)
​​This project investigates the application of the Multiple Reference Frame (MRF) and Sliding Mesh (SM) methods for simulating the aerothermal performance of a rotating wheel and brake disc assembly. The study aims to evaluate the accuracy and computational trade-offs between the steady-state MRF approach and the more computationally intensive, transient SM method, and to determine if a correction factor can be derived to enhance MRF results. The methodology began with the aerodynamic validation of an isolated wheel model against experimental Particle Image Velocimetry (PIV) data, establishing solver settings and mesh independence. Later, a comprehensive model incorporating a 205/55/R16 tyre, rim, and a vented brake disc with pads and caliper was developed. Four steady-state MRF simulations were conducted at varying rotational speeds, and a single transient SM simulation was performed for comparison. Key quantities of interest included the drag coefficient (Cd), heat transfer coefficient (HTC), and temperature distribution. Results indicated that both MRF and SM methods produced aerodynamically valid results for the isolated wheel, with the SM method capturing wake structures with marginally higher fidelity. For the full brake system, significant differences emerged. The SM method predicted a 14.7% higher HTC and a more uniform temperature distribution across the brake disc compared to the MRF result at the same speed, suggesting it more accurately captures the transient convective cooling. A strong linear relationship was observed between rotational speed and HTC in the MRF data. A correction factor was developed and implemented via a User-Defined Function (UDF) to scale the MRF-predicted HTC. While this adjustment successfully brought the maximum temperature prediction to within 2.2% of the SM value, it did not fully replicate the SM results for other thermal variables. The study concludes that while the MRF method offers a computationally efficient approximation, the SM method provides a more physically accurate representation of the convective heat transfer process. A simple single-variable correction factor for MRF is insufficient to fully emulate SM results, as the differences are multi-variate and inherent to the fundamental approaches of each method. Future work should focus on longer-duration SM simulations for robust validation and exploring multi-variable correction methodologies.
Sorrell, Matthew - Industrial Supervisor - Red Bull Technology
Keywords: Computational Fluid Dynamics (CFD); Multiple Reference Frame (MRF); Sliding Mesh; Brake Disc Cooling; Heat Transfer Coefficient (HTC); Aerothermal Analysis; Automotive Aerodynamics